Knowledge transfer through university-industry relations: some aspects of organizational culture. Teadmussiire ülikoolide ja majanduspraktika suhete abil: mõned organisatsioonikultuurilised aspektid - Vadi, Maaja; Haldma, Toomas (Estonian Discussions on Economic Policy, 2010)
The role of national universities and other higher education institutions in knowledge transfer in countries with post-Soviet economies has been studied in very modest extent, especially in the context of small countries. This paper concentrates on the organizational culture aspects playing important role in the commercialization of university research within the university knowledge transfer and knowledge based society framework in Estonia. Knowledge sharing and commercialization depend on nature of organizational culture, as a part of internal environment. Two largest Estonian universities (University of Tartu and Tallinn University of Technology) are compared in various factors influencing knowledge transfer using document analysis and interviews. The present study has shown that knowledge transfer faces numerous issues, and in particular soft issues (individual mindsets and organizational values) may differ from university to university